Financial Fragility and Economic Performance in Developing Economies : Do Capital Controls, Prudential Regulation and Supervision Matter? - Rossi, Marco (IMF Working Papers; Working Paper ;, 1999)
Little empirical investigation exists of the links among capital account liberalization, prudential regulation and supervision, financial crises, and economic development, mainly because of the lack of comparable measures to describe regulatory practices for different countries. This paper examines empirically, albeit in a preliminary manner, these links using new measures of capital controls, prudential regulation, supervision, and depositors' safety for a sample of 15 developing economies over the period 1990-97. Results confirm the importance of the degree of capital account convertibility and the regulatory and supervisory framework in affecting financial fragility and economic performance.